2012
DOI: 10.1371/journal.pone.0043071
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for HIV and Unprotected Anal Intercourse among Men Who Have Sex with Men (MSM) in Almaty, Kazakhstan

Abstract: IntroductionMen who have sex with men (MSM) are at high risk for HIV infection. MSM in Central Asia, however, are not adequately studied to assess their risk of HIV transmission. Methods: This study used respondent driven sampling methods to recruit 400 MSM in Almaty, the largest city in Kazakhstan, into a cross-sectional study. Participation involved a one-time interviewer-administered questionnaire and rapid HIV screening test. Prevalence data were adjusted for respondent network size and recruitment pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 16 publications
4
29
1
Order By: Relevance
“…It was also lower than the results presented in the last report of the Joint United Nations Programme on HIV/AIDS (UNAIDS) (42%) 12 and in the Brazilian multicenter study (49%) 3 and other populations of MSM 42 . This is one of the most important indicators for monitoring the HIV epidemic, since it promotes a link between individuals and health services and can be one of the main entry points for healthcare via counseling and support for persons with HIV and other STI, allowing contact with information and preventive measures.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…It was also lower than the results presented in the last report of the Joint United Nations Programme on HIV/AIDS (UNAIDS) (42%) 12 and in the Brazilian multicenter study (49%) 3 and other populations of MSM 42 . This is one of the most important indicators for monitoring the HIV epidemic, since it promotes a link between individuals and health services and can be one of the main entry points for healthcare via counseling and support for persons with HIV and other STI, allowing contact with information and preventive measures.…”
Section: Discussioncontrasting
confidence: 69%
“…Lower access to lubricant gel was associated with a lifetime history of HIV infection and syphilis, and difficulty in access to lubricant gel has also been reported in other countries in the MSM population 38,42 . Lubricant gel is important for the prevention of HIV infection 12 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Many of the risk factors identified in the RDS survey are also commonly reported worldwide by previous studies (Baral et al, 2009;Berry et al, 2012;Choi, Ayala, Paul, Boylan, & Gregorich, 2013;Zhang et al, 2013). While in the TLS survey, only having a low income and having male sex partners only (vs. having both male and female partners) were associated with HIV infection.…”
Section: Discussionsupporting
confidence: 64%
“…While rates have remained low and relatively stable across much of western and central Europe, with rates rarely above 4% ever having injected,4 5 this drug delivery method has been shown to be more common in central Asia,6 Russia7 and parts of Sub-Saharan Africa 8. Analysis of community survey data from 2011 in Sydney, Australia, found that 5.0% of MSM had injected drugs within the previous 6 months, a figure that is considerably higher than among the general population 9…”
Section: Patterns Of Substance Use Among Msmmentioning
confidence: 99%